1983
DOI: 10.1063/1.332527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface preparation on the 77 K photoluminescence of CdTe

Abstract: Photoluminescence spectra were obtained at 77 K for three undoped CdTe single crystal specimens whose surfaces were prepared by mechanical, conventional chemimechanical, and modified hydroplane polishing techniques, respectively. The hydroplane polished sample was found to be a much brighter source of photoluminescence than either of the other two specimens. In addition, hydroplane polishing produced a photoluminescence spectrum in which nearly all of the emission occurred in a band centered at 1.58 eV rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It is usually ascribed to intrinsic defects/impurities and, consequently, is known as the 'defect band'. Although most research has concentrated on investigating bulk defects, Myers et al [18] showed that surface states could very well be responsible for the shape of the defect band. A number of explanations exist regarding the recombination mechanism involved including band-acceptor (e-A) transitions [17], donor-acceptor-pair (DAP) recombination [9,19,20] and internal transitions within highly localized defects [21][22][23].…”
Section: 21mentioning
confidence: 99%
“…It is usually ascribed to intrinsic defects/impurities and, consequently, is known as the 'defect band'. Although most research has concentrated on investigating bulk defects, Myers et al [18] showed that surface states could very well be responsible for the shape of the defect band. A number of explanations exist regarding the recombination mechanism involved including band-acceptor (e-A) transitions [17], donor-acceptor-pair (DAP) recombination [9,19,20] and internal transitions within highly localized defects [21][22][23].…”
Section: 21mentioning
confidence: 99%
“…Higher oc was observed on all iTAP processed solar cells as compared to the reference device without iTAP. The increased oc may be attributed to the improved CdS/CdTe interface through interdiffusion at the interface [25] facilitated by the iTAP, which is supported by the monotonic increase of the oc with increasing iTAP duration below 20 min. The best oc ∼724 mV was obtained at 15 min.…”
Section: Resultsmentioning
confidence: 77%
“…For the first time, the relatively broad spectral band peaking at 1.476 eV was observed by Dean et al [11]. A number of recombination mechanisms with participation of bulk and surface defects have been proposed to explain this emission [12][13][14][15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 84%